2006
DOI: 10.1007/bf02729017
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity studies of Kherigarh cattle based on microsatellite markers

Abstract: We report a genetic diversity study of Kherigarh cattle, a utility draught-purpose breed of India, currently declining at a startling rate, by use of microsatellite markers recommended by the Food and Agriculture Organization. Microsatellite genotypes were derived, and allelic and genotypic frequencies, heterozygosities and gene diversity were estimated. A total of 131 alleles were distinguished by the 21 microsatellite markers used. All the microsatellites were highly polymorphic, with mean (+/- s.e.) allelic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 25 publications
8
26
5
Order By: Relevance
“…However, considerable high heterozygosity values indicated the existence of substantial genetic variability in the studied population. Similar high values for observed and expected heterozygosity have been observed for Kherigarh (0.71) cattle (Pandey, Rekha, Singh, et al 2006) However, many workers reported comparatively lower mean expected heterozygosity, 0.67 in Tharparkar cattle and Hariana cattle (Rehman & Khan 2009); 0.59 in Deoni cattle (Mukesh et al 2004) and 0.68 in Kherigarh cattle (Pandey, Rekha, Yatender, et al 2006). The mean observed heterozygosity values, though lower than the expected values, exhibited failure of significant differences suggesting random mating in Belahi cattle.…”
Section: Genetic Diversity and Within-breed Genetic Variationsupporting
confidence: 83%
See 3 more Smart Citations
“…However, considerable high heterozygosity values indicated the existence of substantial genetic variability in the studied population. Similar high values for observed and expected heterozygosity have been observed for Kherigarh (0.71) cattle (Pandey, Rekha, Singh, et al 2006) However, many workers reported comparatively lower mean expected heterozygosity, 0.67 in Tharparkar cattle and Hariana cattle (Rehman & Khan 2009); 0.59 in Deoni cattle (Mukesh et al 2004) and 0.68 in Kherigarh cattle (Pandey, Rekha, Yatender, et al 2006). The mean observed heterozygosity values, though lower than the expected values, exhibited failure of significant differences suggesting random mating in Belahi cattle.…”
Section: Genetic Diversity and Within-breed Genetic Variationsupporting
confidence: 83%
“…Most of the loci showed a similar trend in terms of allele numbers with the earlier characterized cattle breeds. The observed number of alleles in Belahi cattle was higher than observed in other Indian breeds (Mukesh et al 2004;Pandey, Rekha, Singh, et al 2006;Pandey, Rekha, Yatender, et al 2006), namely Hariana (6.5), Sahiwal (5.2), Deoni (5.9), Kenkatha (5.95) and Kherigarh (3.77) cattle. Our findings had shown moderately higher number of alleles; this could be due to the presence of higher heterogeneity present in Belahi population.…”
Section: Genetic Diversity and Within-breed Genetic Variationcontrasting
confidence: 53%
See 2 more Smart Citations
“…The main value was 0.009 and it indicates 0.9% gene fixation within the breeds analysed. This value is lower than that obtained by Pandey et al (2006) in the Indian cattle population (0.188). F IT value varied from -0.018 (TGLA227) to 0.371 (ETH10).…”
Section: Resultscontrasting
confidence: 67%